Cyberbullying and Adolescent Neurobiology - McLoughlin, Larisa T.; Lagopoulos, Jim; Hermens, Daniel F. (Frontiers in Psychology, 2020)
Whilst it is well documented that cyberbullying is linked to poor mental health outcomes, limited research has examined how cyberbullying may influence brain development adolescents, and the influence of each of these factors. The paper’s primary objective was to develop an understanding of research to date that addresses any relationship between adolescent brain development and cyberbullying. The current paper reviews any existing literature regarding the impact of cyberbullying on adolescent brain development, paying particular attention to research using Magnetic Resonance Imaging (MRI) techniques. Whilst brain studies have examined neural mechanisms associated with conduct disorders, antisocial behaviour, and aggression in young people; there is a paucity of research examining these factors specifically in relation to cyberbullying. In particular, little research has examined how MRI research could help understand how the brain is affected by cyberbullying, not only in bullies and victims but also bystanders. This paper highlights the gaps in the cyberbullying field in relation to neuroscience research, and the need for further, longitudinal research examining cyberbullying and how it may affect brain development in young people. This paper concludes by suggesting a framework for future research, and highlights the importance of future findings for developing interventions and understanding short and long term effects.